Dig for victory now! 1940 (1940)
1940 1939-1945 "Dig for victory now! 1940" [HFR0204], 1940 The 'Dig for Victory' campaign called for every man and woman in Britain to keep an allotment. Lawns and flower-beds were turned into vegetable gardens. In a time of shortage the sight of so many vegetables, possible from a little gardening, was a tempting sight.